2002
DOI: 10.1002/macp.200290002
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Design via the Interchange of Xanthates (MADIX): Polymerization of Styrene with O‐Ethyl Xanthates as Controlling Agents

Abstract: Control of the free‐radical polymerization of styrene was achieved using a series of eight xanthates of the general structure RS(CS)OEt as reversible addition fragmentation chain‐transfer agents. The influence of the nature of the R leaving group was explored. It was found that the transfer ability of the xanthate is markedly improved with increasing stability of R and its steric hindrance. Group R strongly influences the Mn evolution profile during polymerization, but only influences the polydispersities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
133
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(149 citation statements)
references
References 28 publications
13
133
0
3
Order By: Relevance
“…Systems studied by mass spectrometry include (polymer/ RAFT agents): PNIPAM/20,22, [78] PNIPAM/39,40, [93] PVAc/49, [48] PS/21, [126] PS/69, [106] PMMA/8,11, [100] PBA/ 57,63, [127] PMA/21,22,24, [81,83] PEA/79, [49] and poly-(acenaphthalene)/81. [128] ESI is a softer ionization technique than MALDI-TOF and is more likely to leave the end groups intact to be observed in the mass spectrum.…”
Section: Evidence In Support Of the Raft Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems studied by mass spectrometry include (polymer/ RAFT agents): PNIPAM/20,22, [78] PNIPAM/39,40, [93] PVAc/49, [48] PS/21, [126] PS/69, [106] PMMA/8,11, [100] PBA/ 57,63, [127] PMA/21,22,24, [81,83] PEA/79, [49] and poly-(acenaphthalene)/81. [128] ESI is a softer ionization technique than MALDI-TOF and is more likely to leave the end groups intact to be observed in the mass spectrum.…”
Section: Evidence In Support Of the Raft Mechanismmentioning
confidence: 99%
“…In these circumstances, Fig. 7 will (S), [46] (S) [9] - [16,[105][106][107] (BA), [38] (S) [9] - [16,49,106,107] AA, [108] (MA), [16] (EA), [16,49] AA-AM, [108] AA-b-AM, [108] AM, [108] VAc, [6,16] (S), [16] (BA) [16] AA-AM-b-AM [108] [106] - [16,106] - [16,106] (EA) [16] - [106] (tBA), [6] (MMA) [38] -…”
mentioning
confidence: 99%
“…O-ethyl-S-(1-ethoxycarbonyl)ethyldithiocarbonate (1) was prepared according to the literature. 19 1-Phenylethyl phenyldithioacetate (2) was prepared according to the literature. 32 Mn 2 (CO) 10 (Aldrich, 98%) and Fe 2 Cp 2 (CO) 4 (Aldrich, 99%) were used as received and handled in unlighted glovebox (VAC Nexus) under a moistureand oxygen-free argon atmosphere (O 2 < 1 ppm).…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Among the numerous initiating systems, there are now three representatives in terms of wide applicability and good controllability; i.e., the nitroxide-mediated radical polymerization (NMP), 1,2 metal-catalyzed living radical polymerization or atom transfer radical polymerization (ATRP), [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and reversible addition-fragmentation chain transfer (RAFT) 18 polymerization or macromolecular design via interchange of xanthate (MADIX). 19 Although the components and the mechanisms are different, they are all based on the reversible transient activation of the dormant covalent species into the growing radical species. However, each system has its own characteristics or features due to the differences, which suggests that the choice of initiating systems is important depending on the monomers, conditions, purposes, etc.…”
mentioning
confidence: 99%
“…For MADIX of MAMs, several kinetic studies have been performed with styrene as the monomer. 7,17,19,25,32,34,36,37 For example, Adamy et al 7 investigated the influence of the chemical structure of the initial RAFT agent for MADIX of styrene in toluene and reported that with (O-ethyl xanthate)-2-ethyl propionate (OEXEP) as the initial RAFT agent, a Đ close to 2 (X m = 20%) can merely be obtained. In contrast, by increasing the electron-withdrawing capacity of the Z group by incorporation of fluorinated groups at β-position to the oxygen atom, as for instance in (O-2,2,2-trifluoro ethyl xanthate)-2-ethyl propionate (OtFOX), a lower but still high Đ of 1.6 can be achieved (X m > 20%), in agreement with an earlier experimental study by Destarac et al 36 The latter observation was attributed to an increased reactivity of the SvC bond due to the decreased availability of the oxygen lone pair to conjugate with the thiocarbonyl group.…”
Section: Introductionmentioning
confidence: 99%